A igualdade de gênero na ciência brasileira: um estudo da ocupação feminina nos Institutos Federais de Educação, Ciência e Tecnologia da Região Sudeste - Rocha, Etiene Siqueira (2022)
Science, Technology, and Society (STS) Studies encompass feminist epistemology that is dedicated to the debate on the impact of gender relations in the production of scientific knowledge mainly. In this sense, the main purpose of this study was to trace female participation in S&T, through a study at the Institutos Federais Educação, Ciência e Tecnologia (IF) in the Southeast region of the country from 2008 to 2020. It bases the discussion on the need for (re)existence of public policies for gender equality in S&T outlined since 2004. The specific purposes are to characterize the women who make up the teaching and administrative staff at the IF; to map the participation of women in the administrative and academic management of the IF; to observe the female representation in the research groups and scientific journals of the IF; analyze the academic production of professors holding the IF; to verify the performance of the academic community of the IF from the perspective of gender issues; and looking at female aging in IF, paying attention to factors that may be decisive for their permanence in these spaces. For that, a documental analysis of primary and secondary information sources of public character produced by the Federal Government was carried out, as well as a bibliometric analysis of the academic production of the professors who are professors of the IF. The study pointed out that, throughout the analyzed period, women in the IF were mainly white young women and the increase observed in the number of women present in the IF are still underrepresented in some scientific areas and have made little progress. in positions of greater prominence and academic success. It was also possible to observe that they are a minority in the editorial bodies of journals, with the female participation in scientific committees being less unequal. The professors' academic production indicated a preference for proceeding as well as for the collaborative work that was established with both IF colleagues and external researchers with emphasis on Southeast Region institutions. As for the research groups led by women, it was possible to verify that the figure of the 2nd leader was composed of women, as well as the composition of the groups was equal. It was possible to identify numerous actions focused on the debate of asymmetries in S&T and on the promotion of gender equality in the Southeast Region, with emphasis on the number of activities at the IFSP and IFRJ. However, the IFSULMG, despite the wide academic production, did not present activities focused on gender issues in S&T. The proposed study contributed to the area by bringing light to the participation of women who help in the formation and teaching of S&T in the country. That said, it can be considered that the incorporation of a gender perspective is essential for a change in the S&T paradigm, making scientific and technological knowledge free from gender bias and androcentrism.